Osteoarthritis management in primary care. (25th February 2019) - Finney, Andrew; Lambourne, Hazel; Cottrell, Elizabeth
Abstract : Osteoarthritis is one of the most common forms of musculoskeletal conditions seen in general practice. Not only can it cause pain and discomfort, but it can greatly affect the quality of life of patients who live with this condition Joint pain attributed to osteoarthritis is a leading cause of disability worldwide. In the UK, the burden of osteoarthritis in primary care on both the individual and society is increasing. The National Institute for Health and Care Excellence offer a guideline for osteoarthritis with recommended core treatments that are at the centre of disease management and suitable for all patients. This article will focus on osteoarthritis and its management, and suggest ways in which practice nurses can address joint pain with their patients.